Leadership styles and safety behaviours with safety climate as a mediator among oil and gas workers - Brown, Bara Kabaka (2017)
Existing submissions from industry practitioners and researchers suggest a high rate of occupational accidents, injuries and fatalities occasioned by poor safety and health management systems, and attendant safety-related behaviours in the Nigerian oil and gas industry. In an attempt to improve employees’ safety behaviours, this study investigated the relationship between leadership styles, safety climate and safety behaviours in the Nigerian O & G industry. Specifically, this study examines the influence of authentic leadership, inclusive leadership, safety climate on components of safety behaviours namely, safety compliance, safety participation and risky behaviour. Via a cross-sectional design and quantitative approach, the study was conducted among 319 systematically selected O & G workers in Rivers State, Nigeria. The PLS-SEM tool (SmartPLS 3.0) was used in analyzing the data collected from the respondents. The findings of the study indicated that the direct relationships between authentic and inclusive leadership styles with safety climate were positively significant. Also, the study found direct significantly positive relationships between safety climate and safety compliance and safety participation. However, the relationship between safety climate and risky behaviour was negative. Similarly, safety climate mediated the relationship between the authentic and inclusive leadership styles with safety compliance and safety participation, but not with risky behaviour. Based on the findings, it can be concluded that the authentic leadership and inclusive leadership styles are critical to positively shaping the safety climate perceptions of O & G workers. Positively shaped safety climate perceptions should in-turn determine the positive safety behaviours of the workers. Consequently, theoretical and practical implications, in addition to recommendations for future research are holistically discussed.